Effect of low temperature storage conditions on the viability of microalgae Chlorococcum dissectum - Vozovyk , K.; Shevchenko, N. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2022)
Chlorococcum dissectum Korshikov, 1953 is a unicellular freshwater green alga capable of accumulating and depositing lipids in cells. Regardless of their origin and taxonomic classification, biotechnologically important microorganisms and cell lines are biological resources that are used to produce various products. The aim of the work was to determine the effect of low-temperature storage conditions on the alga viability. The temperatures used were as follows: –18, –40, –70, and –196°C. An ordinary household freezer was used to provide –18°C. Cooling to –40 and –70°C was carried out with uncontrolled cooling rates by placing the cryotubes directly into the freezers or using a Mr. Frosty freezing container, which provides a temperature decrease rate of 1 deg/min. Freezing to –196°C was carried out by direct immersion of cryotubes in liquid nitrogen and two-stage cooling at 1 and 20 deg/min to –40°C with subsequent transfer to a cryostorage. The viability of C. dissectum was determined by counting the colonies formed on BG-11 agarized nutrient medium. It was found that the cells completely lost their viability after freezing to –18°C and storage for two days. Cryopreservation to –196°C for all studied variants and uncontrolled cooling rate to –40 and –70°C, as well as further storage of such samples at these temperatures, led to significant or complete loss of their viability. Cooling in a Mr. Frosty freezer container to –40 and –70°C did not affect the ability of cells to grow. Moreover, storing C. dissectum at –40°C did not cause a significant loss of viability throughout the study period, and its storage at –70°C did not change the viability index at all. The obtained results showed that the controlled cooling and the use of freezers at –40°C and –70°C, respectively, are promising for medium-term and long-term storage of C. dissectum suspension culture. To increase the viability of samples after cooling to liquid nitrogen temperature, it is necessary to develop cryopreservation modes using cryoprotectants.